Hudební oddíly československých legionářů v Rusku 1914–1920 - Tomáš Drábek (Historie - Otázky - Problémy)
The paper discusses the regimental music bands of the Czechoslovak Legion in Russia. It focuses mainly on their tasks, functions and importance. Attention is also paid to the fact that the legionary bands combined elements of Russian and Austro-Hungarian military music. The text addresses the question of which cultural influence ultimately prevailed.